Letter from the Editors: Honoring the Life and Legacy of Justice Ruth Bader Ginsburg - The Editors of Volume 40 of the Columbia Journal of Gender and Law (Columbia Journal of Gender and Law, 2020)
As we publish Volume 40 of the Columbia Journal of Gender and Law, we also mourn the tremendous loss of Justice Ruth Bader Ginsburg ’59—an academic titan, zealous advocate, and powerful force in the legal profession. There is little doubt that her career changed the trajectory of American jurisprudence; her impact on the rule of law is lasting and meaningful. Justice Ginsburg’s legacy is particularly special to us. As a member of our Board of Advisors and alumna of Columbia Law School, Justice Ginsburg has been a guiding light for students serving on our staff since the Journal’s inception thirty years ago. In her introduction to our first issue, Justice Ginsburg described our mission to “portray today’s feminist movement, not as unitary, rigid or doctrinaire, but as a spacious home, with rooms enough to accommodate all who have the imagination and determination to work for the full realization of human potential.” With each piece of new scholarship published, the Columbia Journal of Gender and Law strives to maintain that spacious home for today’s movement for gender equality— especially as it expands, improves, and evolves. It is with respect and gratitude that we continue our work in her spirit.